Agha Mohammed Khan and variables of the political military Kajari state (1779-1797) - Dr. Yousif Taha Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
This period (1779-1797) of the modern history of Iran is especially important, when Iran witnessed authoritarian conflicts that cost the Iranian society a lot of sacrifices after the country became a battleground for fighting, fighting and physical liquidation among the competing forces on the throne of Iran, tribal leaders and leaders in All the Iranian provinces, whether in the north, south, west or center, were the result of the victory of the Qajaris and the establishment of their state, which continued to rule Iran until 1925.